10.1016/s0197-2510(08)70218-3 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: The Therapeutic Greenhouse Program, located at an elementary school in an underserved community, offers a sustainable and reproducible model for school-based garden programming. Developed by a school-based health center, the program integrates medical and behavioral health services within an alternative therapeutic environment. It has been maintained since 2020 through strong partnerships with school staff, families, and community organizations. CONTRIBUTIONS TO PRACTICE: The program bridges hands-on food literacy education with clinical care delivery. Elementary school children engage in structured sessions that combine nutrition education, experiential learning, and behavioral health support within the garden setting. Close collaboration with teachers and community partners embeds the program into the daily school routine, fostering a multidisciplinary approach to student wellness. IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: This model supports policies that expand school-based health services into nontraditional care environments. It demonstrates the feasibility of interdisciplinary collaboration in delivering integrated, experiential health education. Furthermore, the program advances health equity by providing inclusive, nonstigmatizing access to health promotion and fresh food. CONCLUSIONS: By leveraging billable services, strategic partnerships, volunteer engagement, and small-scale revenue generation, the program provides a financially sustainable and replicable framework for integrating healthcare and education in school settings.